Customer Relation Practices and it's Impact on Customer Satisfaction in Travel & Tour Business (A Case Study of Kathmandu Valley) - Khanal, Kapil (Journal of Balkumari College, 2020)
Objective: To understand customer relation practices of Travel & Tour Businesses and measure the customer satisfaction through survey. Methods and Materials: Customer relation practices were recorded through semi-structured interviews and observation of travel agencies in Kathmandu. Furthermore, 119 customer feedbacks from the three agencies were gathered. Feedback was gathered by using a questionnaire. Research is based up on primary data. Simple random sampling technique is used to collect data. Descriptive as well as explorative research designs were used to analyze the data. Results and Conclusion: "Details given to Clients" and "Accurate Information" are the first important factors for travel agents. Attraction of the place and recommendation of travel agent are insignificant. Travel & Tour Business is a part of Tourism Industry which is largest industry in Nepal.